1998
DOI: 10.3171/jns.1998.89.6.0927
|View full text |Cite
|
Sign up to set email alerts
|

Localization of pituitary adenomas by using intraoperative ultrasoound pituitary in patients with Cushing's disease and no demonstrable tumor on magnetic resonance imaging

Abstract: The IOUS is a sensitive imaging modality when used in patients with Cushing's disease in whom findings on pituitary MR imaging are negative. The improved ability to detect and localize these tumors by using IOUS positively affects surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 18 publications
1
46
0
2
Order By: Relevance
“…Zada et al 38 , refieren resecciones completas en un 75% en tumores con una PRL inferior a 200 ng/ml comparables al resto de los autores 35 . En pacientes con enfermedad de Cushing con microadenomas los niveles de remisión se sitúan cerca del 100%, siendo más bajos cuando no hay una imagen evidente preoperatoria, en macroadenomas invasivos y en las reintervenciones 4,34,36 . En pacientes con acromegalia la remisión es de un 75% en los microadenomas y de alrededor de un 50% en los macroadenomas 38 .…”
Section: Discussionunclassified
“…Zada et al 38 , refieren resecciones completas en un 75% en tumores con una PRL inferior a 200 ng/ml comparables al resto de los autores 35 . En pacientes con enfermedad de Cushing con microadenomas los niveles de remisión se sitúan cerca del 100%, siendo más bajos cuando no hay una imagen evidente preoperatoria, en macroadenomas invasivos y en las reintervenciones 4,34,36 . En pacientes con acromegalia la remisión es de un 75% en los microadenomas y de alrededor de un 50% en los macroadenomas 38 .…”
Section: Discussionunclassified
“…About 90% of ACTH-secreting pituitary tumors are microadenomas [Shimon et al, 1998]. In fact, it has been reported that MRI scan do not detect demonstrable tumors in approximately 40% of patients with active Cushing disease [Watson et al, 1998]. Almost all patients with Cushing's disease have an associated ACTH-secreting pituitary adenoma that is the most common cause of endogenous hypercortisolism, accounting for approximately 65-70% of all cases of Cushing's syndrome [Arafah et al, 2001].…”
Section: Classification and Clinical Aspects Of Pituitary Tumorsmentioning
confidence: 99%
“…73,74 TS-IUS for localization and targeted resection of pituitary microadenomas that may not be visualized on preoperative MRI, enhances the safety of exploration, maximizes the removal of macroadenomas, and positively effects the surgical outcome at lower costs. 75,76 However, evaluation of larger series with TS-IUS, and more specific instrumentation available for transsphenoidal applications, will be essential in determining the ultimate value of this promising technique.…”
Section: Factors Increasing Surgical Successmentioning
confidence: 99%